Влияние информации на трендоустойчивость финансового рынка - Куссый, М. Ю. (Культура народов Причерноморья, 2014)
В статье рассмотрены некоторые существенные характеристики рыночной информации. Выявленное влияние этих характеристик на прогнозирование системной устойчивости финансового рынка изложено в виде авторских допущений. Показано, что изменения в информационной рыночной среде возможно количественно измерить с помощью показателя текущей волатильности. У статті розглянуті деякі істотні характеристики ринкової інформації. Виявлений вплив цих характеристик на прогнозування системної стійкість фінансового ринку викладено у вигляді авторських припущень. Показано, що зміни в інформаційному ринковому середовищі можливо кількісно виміряти за допомогою показника поточної волатильності. The article shows that the information as the system attribute of the financial market – is one of the basic sources and the motor almost of all market processes. It was considered some essential characteristics of market information and their impact on the stability of the financial market trends. The concepts of information asymmetry, completeness, uniformity of market information, information aging and stability of trends in the financial market was identified. It was revealed the influence of these characteristics on the forecasting of systemic stability of the financial market is set out in a series of author's assumptions, where the connection between qualitative and quantitative changes in the characteristics of the information with the reflection on the financial market, the determinism of market processes, the depth of the market’s «memory» and trend’s stability were indicated. Assumptions, which were formulated, from a methodological point of view, are allowed for a more reasoned analysis of the processes taking place in the financial markets, and to build adequate models of these processes. It is shown that changes in the market information environment may be quantitatively measured by the index of the current volatility. Future studies may reveal more detailed relationship between the characteristics of information and market volatility on the quantitative level.